Experimental and crystal plasticity finite element study of dynamic shear behavior of CoCrNiSi0.3 medium-entropy alloy - Huiqing Fang; Dan Zhao; Wenjun Wu; Guang Hu; Tao Jin; Ji Qiu; Jianjun Wang; Shengguo Ma; Tuanwei Zhang; Zhihua Wang (Journal of Materials Research and Technology, 2024)
Single-phase CrCoNi-based medium-entropy alloys (MEAs) have garnered considerable attention as a promising class of metallic materials. However, despite this growing interest, the dynamic mechanical response of CrCoNi-based MEAs at high strain rate remains controversial. The dynamic shear mechanical behavior of CoCrNiSi0.3 was characterized through Hopkinson-bar experiment utilizing hat-shaped specimen. In this study, a damage model based on the maximum shear strain of each slip system was chosen to describe the damage initiation and evolution. Combined with this micro-scale damage and dislocation density-based crystal plasticity theory, two constitutive models were proposed to perform predictions of the dynamic shear behavior of CoCrNiSi0.3. The strain rate effect, adiabatic temperature rising, damage evolution, and twin volume fraction during dynamic shear deformation were tracked by investigating the influence of resolved shear stress, dislocation density, texture evolution, and twinning systems shear strain. The presented model effectively predicts the deformation state of specimen, the formation and evolution of Adiabatic Shear Bands (ASBs), and the variations in strain rate and temperature at different locations within the shear region. Adiabatic Shear Bands and texture evolution are caused by the local dislocation density rising and misorientation distributions.